Dynamic Changes of Amplitude of Low-Frequency Fluctuations in Patients With Diabetic Retinopathy - Huang, Xin; Wen, Zhi; Qi, Chen-Xing; Tong, Yan; Shen, Yin (Frontiers in Neurology, 2021)
Abstract Background: There is increasing evidence that diabetic retinopathy (DR) patients have a high risk of cognitive decline and exhibit abnormal brain activity. However, neuroimaging studies thus far have focused on static brain activity changes in DR patients; the characteristics of dynamic brain activity in patients with DR are poorly understood. Purpose: This study aimed to investigate the abnormal time-varying local brain activity in patients with DR by using the amplitude of low-frequency fluctuation (ALFF) method combined with a sliding-window approach. Materials and methods: Thirty-four DR patients (18 men and 16 women) and thirty-eight healthy controls (HCs) (18 males and 20 females) closely matched in age, sex, and education underwent resting-state magnetic resonance imaging. The ALFF with sliding-window analyses method was used to compare differences in dynamic intrinsic brain activity between the two groups. Results: Compared with HCs, DR patients exhibited increased dynamic ALFF (dALFF) variability in the right brainstem, left cerebellum_8, left cerebellum_9, and left parahippocampal gyrus. In contrast, DR patients exhibited decreased dynamic ALFF (dALFF) variability in the left middle occipital gyrus and right middle occipital gyrus (voxel-level P<0.01, Gaussian random field correction, cluster-level P<0.05). Conclusion: Our study highlighted that DR patients showed abnormal temporal variability of dALFF in the visual cortices, cerebellum, and parahippocampal gyrus; these findings suggest impaired visual and motor and memory function in DR individuals. Thus, abnormal dynamic spontaneous brain activity might be involved in the pathophysiology of DR.